Towards analysis on textual inference at ASSIN-2 dataset - da Silva, Felipe O.; Craveiro, Giovana Meloni; da Silva, Vinícius F.; Vanzin, Vinícius João de Barros (Anais do Simpósio Brasileiro de Tecnologia da Informação e da Linguagem Humana (STIL); 2023: Anais do XIV Simpósio Brasileiro de Tecnologia da Informação e da Linguagem HumanaDO - 10.5753/stil.2023.234210, 2023)
In this article, we conduct a preliminary analysis of different methods to address the Textual Entailment Recognition (RTE) task in Portuguese. We use the ASSIN-2 dataset as a benchmark to evaluate our models. Our work combines various textual representation approaches, including bag of words and word embeddings, with machine learning models. Additionally, we present a rule-based approach. Our highest performance was achieved by the BERTimbau-large model fine-tuned on ASSIN-2, which attained an F1 score of 0.89%, positioning it just 1% below the current state-of-the-art. Our ongoing experiment aims to combine our different approaches to leverage their full potential.